Maternal Vitamin D3 Status and Association with Low Birth Weight Infant - Raghad Farhad Ahmad; Hanaa Al.Ani (Hawler Medical University, 2018)
Background and Objective: Maternal vitamin D levels may affect fetal growth and cause adverse pregnancy outcomes including low birth weight in neonatal stage. This study was designed to evaluate and determine if the deficiency of maternal Vitamin D associated and affected the growth development of birth weight of neonates. Methods: This study was carried-out on 200 neonates through a cross-sectional study, that used data from the nursery ward at maternity teaching hospital hospitals in Kurdistan, Iraq during a one year period from March 2016 to March 2017. The neonates were divided into two group two groups, neonates with birth weight< 2500 gr (n=45) and neonates with birth weight>2500 gr (n = 55). We depend on the data classifications on medical history, physical examination using a questionnaire method for neonate classifications. Birth time blood samples of their mothers were analyzed for serum 25-(OH)-vitamin D using enzyme linked immunosorbent assay method. Maternal vitamin D status was compared in the two groups. Results: The mean maternal vitamin D level was 24 nmol/L. for mothers with low birth weight and 22 (48.89 %) for mothers with vitamin D deficiency. Seventeen (37.77 %) and 6 (13.34 %) of the mothers with low birth weight had insufficient vitamin D and 6 (13.34 %) had normal Vitamin D levels. The mothers with normal birth weight had a mean vitamin D level of 38.10 nmol/L and the mothers of low levels reached to 10 nmol/L (18.18 %), those of insufficiency vitamin D was 20 nmol/L (36.36 %) and those of sufficient vitamin D 25 nmol/L (45.46 %). Conclusion: Mothers with low vitamin D levels are more likely to have neonates with low birth weight. Increasing the vitamin D levels through nutrition is important for improving the neonatal body weight.